Technology has advanced so much that it allows to see high contrasts - Orbe, Tania; Reyes, Alejandro (#PerDebate, 2018)
The quality of the image in cinema and television is getting closer to the reality that the human eye perceives. The product manager of Sony Latin America, Alejandro Reyes, explains the scope of the 4k technology, its application in the Russia 2018 World Cup and future projections with the experimentation of 8k for the 2020 Olympics. 4k quadruples the resolution (of HD) to offer sharper frames, with more contrasts, resolution and wider color space. Now, the processes of transmission are simpler for companies by different means used as internet, etc.
Keywords: 4k technology; image; contrast; camera; film and television